Edaphic factors and entomopathogenic nematodes in a neotropical banana agroecosystem - Vidaurre Barahona, Daniela (2020)
Introduction: In Costa Rica the banana is one of the most important crops in terms of production and exports; the application of pesticides is hence necessary to control the effect of pests on the plantation, such as the Cosmopolites sordidus black weevil. Because of the harmful effects of pesticides on human and environmental health, and the possibility that pests become resistant to these substances, alternatives compatible with the environment, as potential biological controllers, have been investigated to complement the effect of agrochemicals. The entomopathogenic nematodes (EPN) of genera Heterorhabditis and Steinernema have become a focus of study in the field of biological control because of their symbiotic relation with bacteria of genera Photorhabdus and Xenorhabdus, which are a complex capable of eliminating host insects in hours. Objective: The objective was to determine the presence of EPN of genera Heterorhabditis and Steinernema in soil samples taken from banana plantations in the Caribbean region of Costa Rica, and to characterize their habitat. Methods: Sampling points were selected within the plantations and surrounding areas; physicochemical and microbiological analyses were undertaken (pH, acidity, organic matter, Ca, K, Mg, P, Fe, Cu, Zn, Mn, texture, biomass and microbial respiration of the soil, EPN isolation). Variables were analyzed statistically to determine differences between them, in sampling sites, and samples with presence and absence of EPN. A principal-component analysis (PCA) was undertaken using the variables of greater influence in both categories to find their combinations that would explain their presence according to habitat conditions. A discriminant analysis was undertaken to determine the efficiency of the variables selected in the diagnosis of nematode occurrence. Results: The variables related to the presence of EPN were shown to correspond to organic matter, carbon biomass and microbial respiration. Of the samples 38.4 % were found to be positive with respect to the presence of EPN, of which 95 % correspond to genus Steinernema and the remaining 5 % to Heterorhabditis. According to the quadratic discriminant equation, from 81.2 % of the samples without nematodes, six belong to the group with their presence, whereas for those with EPN, 55.0 % (nine of 20) belong to the absence group. Conclusions: No statistical difference was found between the selected sampling habitats (P = 0.4296); the three variables mentioned above were thus determined have an influence on the presence of EPN; their large values indicate favorable conditions for their persistence.